Anti-Predator Training and Subsequent Survival of Captive-Held Juvenile Meadow Voles (Microtus Pennsylvanicus) - Wiggins, Brittney L (My University, 2012)
Identifying a cost efficient and effective anti-predator training program for captive-held or captive-bred animals is important for developing strong reintroduction programs. Since many reintroduction programs have high mortality due to predation, successful reintroduction programs may rely on reestablishing important anti-predator behaviors through training programs. Post-release survival is monitored, but perhaps is not monitored stringently enough, and many papers that have reported the effects of training have not done subsequent releases. The meadow vole (Microtus pennsylvanicus) is a small, abundant rodent that can be used as a model organism for threatened or endangered species of similar size and ecological importance. For this research, voles underwent a training program where thirteen individuals were exposed to a gray wolf (Canis lupus) scented cloth and a rubber band shot. While trained and control voles had no difference in the number of explorations, trained voles learned from their training sessions as was shown by their responses to a very different predator cue: a red-tailed hawk (Buteo jamaicensis) call or silhouette. Control animals had similarly high responses to a call or silhouette prior to training sessions, whereas trained animals increased their responses from pre- to post-training tests. To further determine the effects of training on survival, all voles were released into three one-acre enclosures in the Winnebago County Parks system. Voles had been ear tagged with unique identification numbers and survival was monitored via mark-recapture techniques. While results were not significant, trained voles and wild voles showed a trend to survive slightly better than control voles. A larger sample size may better elucidate the nuances of this trend. This research, along with other studies, suggests that training may have an impact on survival and should be implemented in captive breeding programs that have animals targeted for release.
A Thesis Submitted In Partial Fulfillment of the Requirements For the Degree of Master of Science-Biology